Pengaruh Model Pembelajaran Kooperatif Berbasis Hands On Activity Terhadap Hasil Belajar IPA - Nasrah Nasrah; Riska Amaliah (STKIP Andi Matappa Pangkep, 2021)
The purpose of this research is to find out the influence of Cooperative learning model based on Hands On Activity on the results of learning Natural Sciences (SCIENCE) in elementary school. Type of research used quantitative research with experimental method (true experimental design) with posttest-only control design. The instruments used to collect data are posttests and observation sheets of student activities. The results showed that the data were analyzed using descriptive analysis and inferenceal analysis. The data were analyzed using descriptive analysis techniques known average value (mean) 73.74 and was in the low category of 43.48% while the average (mean) posttest was 86.96 was in a very high category of 91.32% the average value in posttest class experiments was higher than the average posttest value of control class and inferential statistical analysis using t test formula, it can be known that the calculated tvalue is 4,573 with (df) of 46 – 1 = 45, at a significant level of 5%, so it can be concluded that there is an influence of the Hands On Activity learning model on science learning outcomes in elementary school students.